Demonstrating and Investigating the Mechanical Strength of Solar Cells - V. Ravi Raj; R. Krishna Priya; K. V. Bindu; N. Prabhu; S. Madhavarao; G. Ramkumar; A. H. Seikh; M. H. Siddique; Endalkachew Mergia Anbese (International Journal of Photoenergy)
This study reports on the silicon photovoltaic cells with such an alumina metallization. The photovoltaic cell’s silicon component was subjected to an effective stress studied using a simulation model built with this information. In order to evaluate the efficiency of photovoltaic cells on both sides, as well as in two distinct orientations, a four-point bending experiment analysis was carried out using the model. The side and direction of loading have a significant impact on both strength and fracture. There is tensile stress going perpendicularly along the busbars; the back side of the test specimen had the lowest measured strength.